Fugue in Sacred Vocal-instrumental Compositions of Latvian Composers - Rozenbaha, Ieva (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
The aim of the article is to familiarize with the use of fugue and other fugue-type forms in sacred vocal-instrumental compositions of Latvian composers. The usage of fugues and other related forms in the contemporary sacred music genres is predetermined by the historical tradition. Already since the baroque era one of the most important constructive components of sacred vocal-instrumental compositions is fugue. As regards the Latvian music, the fugue has presented itself forthe first time particularly in the sacred vocal- instrumental composition. Namely the Garīgā kantāte (Sacred Cantata, 1887) by Andrejs Jurjans. After A. Jurjans other composers have used fugue in their sacred vocal-instrumental music: Viktors Bastiks in Requiem (1979), Romualds Kalsons in oratorium Petrus (1993), Rihards Dubra in cantata Canticum fratris solis (1997), Romualds Jermaks in Requiem (2002), Ilona Brege in Requiem (2010) etc.